Characterization of a high‐growth‐rate mutant strain of Pyropia yezoensis using physiology measurement and transcriptome analysis. Issue 3 (1st April 2019) - Ma, Yingchao; He, Linwen; Huan, Li; Lu, Xiaoping; Wang, Guangce
Abstract : A mutant strain of Pyropia yezoensis, strain E, was isolated from the free‐living conchocelis of a pure strain (NA) treated with ethyl methane sulfonate. The incremental quantities of young strain E blades were higher than those of NA after 14 d of cultivation, indicating that young blades of mutant strain E released more archeospores. The mean length and weight of large E blades were both over three times greater than those of NA after 4 weeks of cultivation. The photosynthetic parameters (Fv/Fm, Y[I], Y[II], and O2 evolution rate) and pigment contents (including phycoerythrin and phycocyanin) of strain E blades were higher than those of NA ( P  < 0.05). The cellular respiratory rate of strain E blades was lower than that of NA ( P  < 0.05). In order to investigate the causes of changes in strain E blades, total RNA in strain E and NA blades were sequenced using the Illumina Hiseq platform. Compared with NA, 1, 549 unigenes were selected in strain E including 657 up‐regulated and 892 down‐regulated genes. According to the physiology measurement and differentially expressed genes analysis, cell respiration in strain E might decrease, whereas anabolic‐like photosynthesis and protein biosynthesis might increase compared with NA. This means substance accumulation might be greater than decomposition in strain E. This might explain why strain E blades showed improved growth compared with NA. In addition, several genes related to stress resistance were up‐regulated in strain E indicating that strain E might have a higher stress resistance. The sequencing dataset may be conducive to Pyropia yezoensis molecular breeding research.